Analisis Penerapan Target Costing Dalam Pengendalian Biaya Produksi Untuk Efisiensi Proses Produksi Pada UD. Sumber Rejeki - Lomboan, Treysia Yuliani; Pusung, Rudy J.; Mintalangi, Syermi S. E. (Manajemen Bisnis dan Keuangan Korporat, 2025)
To be able to get maximum profit is the general goal of a company. Cost is one of the factors that affect profit, so the company must understand the financing process properly in order to maximize profit and reduce production costs. The purpose of this study is to determine how the application of target costing as a tool to control production costs and how the application impacts UD. Sumber Rejeki. The research method used is qualitative research that uses descriptive analysis. By using the target costing method, it can have an impact on increasing profits where the profit obtained by the company was previously 50% and increased to 60% after the target costing method was applied, in accordance with the company's expectations.